Pengaruh Training & Development, Collectivism Based Organizational Culture, dan Career Development Terhadap Work Performance dengan Organizational Commitment Sebagai Variabel Mediasi - Novia Kartika Sari (Transpublika Publisher, 2025)
This study aims to investigate the impact of Training & Development (T&D), Career Development (CD), and Collectivism-based Organizational Culture (COC) on Organizational Commitment (OC) and Work Performance (WP) at the Communication and Information Office (Kominfo) of South Tangerang City. The majority of respondents are female (56.9%), within the productive age range (25–40 years), and have a medium tenure (4–12 years), reflecting a workforce profile that is capable of supporting digital transformation and public service delivery. Descriptive analysis shows that respondents hold positive views on TD, CD, COC, OC, and WP, with a focus on skill development, group support, and individual contributions to the organization’s shared goals. The study employs the PLS-SEM method to test the validity, reliability, and relationships between variables. The results indicate that all indicators meet the criteria for validity and reliability. The inner model analysis shows that T&D and COC have a positive impact on OC, while CD has a positive impact on WP. Organizational Commitment mediates the relationship between T&D, COC, and WP, but does not mediate the relationship between CD and WP. Based on the Importance-Performance Matrix Analysis (IPMA), the main recommendation is to improve the TD program, which, despite its high importance, still shows low performance. Meanwhile, CD and OC already exhibit good performance and should be maintained. These findings emphasize the need for more consistent and effective training programs to optimize work performance.